Mobile and business - Baharuddin, Muhammad Nazrul Alif; Mohsin, Muhammad Izzuddin; Mohd Yazid, Muhammad Sahadan; Ramli, Muhammad Zulfahmi; Mohamad, Amir Imtiaz; Sh Salleh, Muhammad; Nathan, Shelena Soosay (Penerbit UTHM, 2021)
Nowadays, many companies use Web and e-commerce to move forward with the time. Usually Mobile Business or Mobile e-commerce and M-commerce related to online sales transactions, especially in monetary value, but uses wireless or mobile electronic devices. When it comes to advances, there will always be new problems that exist especially in e-commerce for individuals, companies, governments, and other entities. One significant area of technological advancement is the development of mobile e-commerce, which encompasses interactive business activities and processes related to a (potential) commercial transaction conducted through communications networks that interface with wireless devices. These systems provide the potential for organizations and users to perform various commerce-related tasks without regard to time and location (anytime from anywhere). This paper identifies and discusses some of the issues related to e-commerce in current and in the future. Our discussion finds categories that include technological issues, challenges in future, and implementation e-commerce for the future.